Development of the initial sunflower breeding material resistant to new high virulent races of broomrape and false powdery mildew - O. F. Gorbachenko; F. I. Gorbachenko; T. V. Usatenko; N. S. Luchkin; E. G. Burlyaeva; N. A. Zhitnik; V. D. Gorbachenko (Зерновое хозяйство России)
The widespread violation of scientifically based crop rotation and their saturation with sunflower caused an accelerated emergence of more aggressive races of broomrape and powdery mildew. Currently, the researchers from different countries have identified 8 races of broomrape A, B, C, D, E, F, G, H. The sunflower varieties and hybrids previously developed at the station and introduced into the State List of Breeding Achievements of the Russian Federation that are resistant to the broomrape races A, B, C, D, E were greatly affected. Monitoring of the races of broomrape and false powdery mildew, conducted by the ARRIOC researchers, showed the presence of more aggressive broomrape races (F, G, H) and false powdery mildew (330, 710, 730) in the fields of the Rostov Region. The current situation necessitated the development of sunflower hybrids resistant to the new aggressive races of these pathogens. To identify such hybrids, the corresponding initial breeding material has been required. It was important to combine resistance to broomrape and false powdery mildew with other breeding-valuable traits in one genotype. The current paper presents the results of the sunflower initial breeding material on resistance to broomrape and false powdery mildew. The work was carried out in the fields and in the laboratories of DOS, an affiliate of the FSBSI FSC ARRIOC. The breeding material developed at the station was used as the initial material. Using hybridization methods, multiple self-pollination, and reliable estimation of pathogen resistance at all stages of the breeding process, there was selected a promising linear material (I-4/4640, I-4/4764, I-5/2450, I-5/2465 and etc.), which was included into the search for high heterosis hybrid combinations. The hybrid combinations developed with its participation (MLG 45/4640, MLG 121/4764, MLG 65/2444, etc.), when estimated on the fields infected by sunflower broomrape, showed a higher resistance to highly virulent races of the pathogen in comparison with the best foreign hybrids.